Hydrometric Behavior of Water Springs Located Along the Driving Tunnel of the El Encanto Hydropower Project - Ramírez, Pablo (2011)
This article analyzes the hydrometrical behavior of the springs located along the El Encanto Hydroelectric Proyect Conduction Tunnel developed by CNFL along the Aranjuez River. Hydrometrical behaviors are analyzed through bimonthly measurements for one year from the springs located along the line of the tunnel and its geopedological properties were analyzed by sampling sites of the outcrop. Having established the hydrometrical dynamic and establishing a relationship with the hydrogeological characteristics of the site, the article presents conclusions about the impact of tunnel construction in the springs and the possibility of groundwater resource impact.